Upaya Peningkatan Tingkat Pengetahuan Siswi MAN 2 Palembang Mengenai Sindrom Pra Menstruasi - Muhammad Aditya Alfarizki; Mitayani Purwoko; Ratih Pratiwi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
Premenstrual syndrome characterized by affective, physical, and behavior symptoms with moderate to severe grade, that usually recurrent every luteal phase of menstrual cycle and disappear within menstruation. The frequency of premenstrual syndrome is still high, in Indonesia and all over the world. To overcome this situation, there should be a health promotion. The aim of this community service was to increase the girl’s knowledge of premenstrual syndrome. This community service was held in one day on November 2016 in public islamic high school MAN 2 Palembang. The schedule was start with pre test consist of 15 questions, counseling sesssion using power point media, discussion session, and post test consist of the same questions to measure the knowledge after counseling. Pre test score showed that 13.9% students had good knowledge and post test score showed an increase of good knowledge (66.7%). Conclusion, heatlh education through counseling method bring a change of knowledge.